Azo-Based Iridium(III) Complexes as Multicolor Phosphorescent Probes to Detect Hypoxia in 3D Multicellular Tumor Spheroids - Sun, Lingli (Sci Rep, 2015)
Hypoxia is an important characteristic of malignant solid tumors and is considered as a possible causative factor for serious resistance to chemo- and radiotherapy. The exploration of novel fluorescent probes capable of detecting hypoxia in solid tumors will aid tumor diagnosis and treatment. In this study, we reported the design and synthesis of a series of “off-on” phosphorescence probes for hypoxia detection in adherent and three-dimensional multicellular spheroid models. All of the iridium(III) complexes incorporate an azo group as an azo-reductase reactive moiety to detect hypoxia. Reduction of non-phosphorescent probes Ir1-Ir8 by reductases under hypoxic conditions resulted in the generation of highly phosphorescent corresponding amines for detection of hypoxic regions. Moreover, these probes can penetrate into 3D multicellular spheroids over 100 μm and image the hypoxic regions. Most importantly, these probes display a high selectivity for the detection of hypoxia in 2D cells and 3D multicellular spheroids.